Upaya Meningkatkan Kepuasan Kerja dengan Kompensasi dan Lingkungan Kerja pada Industri Textil - Syahpudin, Anggi Wahyu; Nuryanti, B. Lena; Utama, Rd. Dian Herdiana (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2017)
The purpose of this paper is to determine the effect of compensation and working environments on job satisfaction. The study was conducted in a period of less than one year, the study is cross-sectional design. And the method used is survey explanatory, and a population of 116 employees. The analysis technique used is multiple linear regression in though using SPSS 23.0. the questionnaire used as a research instrument to collect data from respondents. The finding of this paper is job satisfaction of employees affected by the compensation and working environment significantly and positively. The originality of this paper is compensation and working environment is used as a way to improve employee job satisfaction. This study aimed to describe the compensation, work environment on employee job satisfaction, compensation and work environment influence on job satisfaction to employees in the production of textiles in Bandung. The object that becomes the unit of analysis in this study were employees of the textile production in Bandung. The independent variable in this study is the compensation and work environment, as well as the dependent variable is employee satisfaction.